Efforts towards the synthesis of microsporin B: ready access to both the enantiomers of the key amino acid fragment - Swaroop, Pandrangi Siva; Tripathy, Sibanarayan; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (Tetrahedron Letters, 2014)
Both the isomers methyl-(2S,8R)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate and methyl-(2S,8S)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate of an unusual amino acid residue and the key fragment of microsporin B are prepared. The key steps include cross metathesis and enzymatic kinetic resolution. In addition, a linear tetrapeptide with desired components towards total synthesis is also reported. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cross metathesis; Enzymatic resolution; HDAC inhibitor; Microsporin; Tetrapeptide